L’anthropologie théologico-politique de Thomas Hobbes et les grands changements dans la conception de la loi de nature et du droit naturel au XVIIe siècle anglais - Untea, Ionut (Anales del Seminario de Historia de la Filosofía, 2020)
The overall goal of the article is to reexamine Hobbes’s concern to respond to the challenges of the republican perspective on the relationship between the liberty of subjects and the political power. If, according to Skinner, republican theorists appealed to sources of classical antiquity, I argue that Hobbes chooses to offer a blend of classical and theological ideas in order to generate a “science” of the political life within the confines of a postlapsarian world dominated by passion and the fear of death. If the image of God is maintained in the Hobbesian politics, it is because Hobbes needed a model of imitation of a stability that the individuals dominated by passions failed too often to have. Hobbes also needed a model of omnipotence and providence to be imitated by the sovereign. This complex relationship between the theological heritage of the past and the novelties inaugurated in political thought by Hobbes’s accent on human passions triggers a series of changes in Hobbes’s understanding of the law of nature and natural right. The article brings to discussion Hobbes’s indebtedness to Lactantius in reading Lucretius’s materialism, Augustine’s model of God as a Creator and the theological controversy between intellectualism and voluntarism when formulating his own anthropological perspective on “natural” and “civil” law and right.